A critical review of the US Senate examination report on the 2021 US Capitol riot - Kim, Hakkyong; Lee, Julak (Frontiers in Psychology, 2023)
The US Capitol riot on January 6, 2021, is currently regarded as an unprecedented armed occupation of the US Capitol that left an irreparable stain on the history of American democracy. Five months later, as part of reflective practice, the US Senate released an examination (review) report on the response failures of federal and local law enforcement agencies, along with corresponding recommendations. This research seeks to critically analyze not only response failures but also recommendations made by the US Senate with a comprehensive theoretical framework incorporating concepts of (1) legitimacy and power, (2) procedural justice, and (3) crowd psychology and the protest policing model. In the end, the research tries to present a practical cooperative dialogue or at least a dialogic approach as a means of strengthening legitimacy based on procedural justice, given that not only European countries but also the Republic of Korea currently operate ‘(Korean and Swedish) Dialogue Police’ and (British) ‘Police Liaison Officer’ in practice.